2017
DOI: 10.4103/pm.pm_134_17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thymoquinone on nuclear factor kappa B levels and oxidative DNA damage on experimental diabetic rats

Abstract: Background:Thymoquinone (TQ), the basic bioactive phytochemical constituent of seed oil of Nigella sativa, is one of these herbal drugs known for antidiabetic effects. This study was carried out to assess the effects of the possible role of TQ on nuclear factor kappa B (NF-κB) and oxidative DNA damage levels in experimental diabetic rats.Materials and Methods:Twenty-eight male Wistar Albino rats (200–250 g) were used as experimental subjects. The rats were divided into four groups, including the control, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In this study, it was found that the serum glucose level decreased in the TQ and BAIBA groups. This result coincides with the data in the literature (Kanter, 2009;Omran, 2014;Shi et al, 2016;Usta & Dede, 2017).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas/307supporting
confidence: 92%
“…In this study, it was found that the serum glucose level decreased in the TQ and BAIBA groups. This result coincides with the data in the literature (Kanter, 2009;Omran, 2014;Shi et al, 2016;Usta & Dede, 2017).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas/307supporting
confidence: 92%
“…Essential oil extracted from N. sativa seeds with higher thymoquinone content showed stronger antioxidant activity than other essential oils ( Abedi et al, 2017 ). In this context, Usta and Dede (2017) assessed role of thymoquinone on oxidative DNA damage and NF-κB levels in diabetic rats. The results revealed that the oxidative DNA damage (8 hydroxy-2-deoxyguanosine) and NF-κB levels were insignificantly lowered after treatment.…”
Section: Biological Activities: Preclinical In Vitro/in Vivo Studies Of the Genus Nigella And Activmentioning
confidence: 99%
“…It was related to the capacity of thymoquinone to increase insulin sensitivity in insulin-resistant HepG2 cells through a SIRT1-dependent mechanism ( Karandrea et al, 2017 ). Glycemic parameters were momentously controlled by the administration of thymoquinone (8) to the diabetic rats ( Usta and Dede, 2017 ). El-Aarag et al (2017) also investigated the effects of this compound to boost anti-diabetic properties of metformin in streptozotocin-induced diabetes in male rats.…”
Section: Biological Activities: Preclinical In Vitro/in Vivo Studies Of the Genus Nigella And Activmentioning
confidence: 99%